Compounding Prevalence of Inflammatory Bowel Disease in a 2024 Population‐Based Study From Canterbury, New Zealand - Angela J. Forbes; Andrew S. Day; Chris M. A. Frampton; Richard B. Gearry (JGH Open, 2025)
ABSTRACT Background and Aim The epidemiological patterns of inflammatory bowel disease (IBD) can give insights into disease etiology and health system burden. This study aimed to measure the population‐based prevalence in Canterbury and consider the region's position within the 4‐stage epidemiological model of IBD. Methods Gastroenterology clinics in Canterbury were searched for patients with a confirmed diagnosis of IBD. Demographic and disease details (including Montreal phenotype) were extracted from individual medical records. The prevalence of IBD, Crohn's disease (CD), ulcerative colitis (UC) and inflammatory bowel disease unclassified (IBDU) was established for the total population and for age, sex, and ethnic sub‐groups. Results Altogether 4042 individuals (1 in 150 people) in Canterbury with IBD were identified. The point prevalence of IBD on 1st January 2024 was 671 (95% CI 651–692) per 100 000 persons. The prevalence of CD 386 (95% CI 370–402) was higher than UC 264 (95% CI 251–277) each per 100 000. Almost three times as many individuals had IBD in 2024, compared to a 2005 study. The majority of the cohort were New Zealand European (92.9%) followed by Māori (4.2%), Asian (2.6%) and Pacific peoples (0.3%). Older adults (65+ years) comprised 21% of the population with a prevalence of 845 (95% CI 789–904) per 100 000 persons. Conclusion Canterbury has the highest reported prevalence of IBD in Oceania to date, and there is a growing proportion of older age patients. The rapid rise in cases supports the hypothesis that Canterbury is in the compounding prevalence stage of the epidemiological model of IBD.